A Short Note on Transverse Vibrations of a Shaft Carrying Two (or One) Disk Excited by a Nonideal Motor - Felix, J. L. Palacios [UNESP]; Balthazar, José Manoel [UNESP]; Brasil, R. M L R F (Asme-amer Soc Mechanical Eng, 2009)
The paper presents a number of numerical simulations of the transverse vibrations of two (or one) imbalanced rotors forced by an electric motor with limited power supply, during the passage through of the two resonance zones (increasing and decreasing input voltages). The predominant presence of the Sommerfeld effect. when the rotational velocity of the motor is captured, in the second resonance frequency is demonstrated. We have shown that the hysteretic jump phenomenon exists in a rotor system with two (or one) disks, and with this, we have shown that a torque is influenced by the dynamical behavior of die rotor [DOI: 10.1115/1.3007979]
Keywords: limited power supply; nonideal vibrations; transverse vibrations; disks; sommerfeld effect